Application of Break Even Point Method as Profit Planning at UD Sinar Harapan Cracker Krecek Factory - Azizah, Islami Dien; Fauji, Diah Ayu Septi; Purnomo, Hery (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: analyze break even points at UD Sinar Harapan as a profit planning tool. Design / Method / Approach: this study uses a descriptive quantitative approach with survey, interview, and observation methods. Research aim: This research aims to analyze break-even points at UD Sinar Harapan as a profit planning tool. Design / Method / Approach: This study uses a descriptive quantitative approach with survey, interview, and observation methods. Research Finding:  the results of the study obtained profit planning calculations by referring to the previous year's profit with a future profit target of 20%. So, for this target to be realized, UD Sinar Harapan must sell 123,682 kg in 2023 with a revenue of Rp. 1,793,592,778. From the results of the application of the Break Even Point method conducted by researchers, UD Sinar Harapan's contribution margin shows that it can cover fixed costs in getting business profit or profit. UD Sinar Harapan sales also reached the Break Even Point or broke even from 2020, 2021, to 2022 in units and rupiah. From here UD Sinar Harapan gets its profit.